Diagnostic and prognostic value of CSF neurofilaments in a cohort of patients with motor neuron disease: A cross‐sectional study. Issue 8 (20th February 2021) - Gagliardi, Delia; Faravelli, Irene; Meneri, Megi; Saccomanno, Domenica; Govoni, Alessandra; Magri, Francesca; Ricci, Giulia; Siciliano, Gabriele; Pietro Comi, Giacomo; Corti, Stefania
Abstract: Motor neuron disease (MND) is a rare group of disorders characterized by degeneration of motor neurons (MNs). The most common form of MND, amyotrophic lateral sclerosis (ALS), is an incurable disease with a variable rate of progression. The search of robust biomarkers able to discriminate among different ALS forms is paramount to properly stratify patients, and to identify those who could most likely benefit from experimental therapies. Phosphorylated‐neurofilament heavy chain (p‐NfH) and neurofilament light chain (NfL) are neuron‐specific components of the cytoskeleton and may represent reliable markers of neuronal injury in neurological disorders. In this study, we described our cohort of ALS patients in order to investigate whether and how cerebrospinal fluid (CSF) p‐NfH and NfL levels may reflect progression rate, MN involvement and the extent of neurodegeneration. CSF p‐NfH and NfL were significantly increased in ALS compared with healthy and disease controls, including patients with other forms of MND, and were higher in patients with more aggressive disease course, reflecting progression rate. We also evaluated neurofilament diagnostic accuracy in our centre, identifying with high sensitivity and 100% specificity cut‐off values of 0.652 ng/mL for CSF p‐NfH ( P  < .0001) and of 1261 pg/mL for NfL ( P  < .0001) in discriminating ALS from healthy controls. CSF neurofilaments were significantly correlated with ALS progression rate. Overall, CSF neurofilaments appear to reflect the burden of neurodegeneration in MND and represent reliable diagnostic and prognostic biomarkers in ALS.